2023
DOI: 10.1002/hsr2.1061
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of amyloid and ameloblast‐associated proteins to odontogenic cysts and tumors: A cross‐sectional study

Abstract: Background and Aims Odontogenic cysts and tumors often form hard and soft structures that resemble odontogenesis. It is well known that amyloid is produced in Pindborg tumors; however, it is still debatable whether it is also formed in other odontogenic tumors and cysts. This study aimed to detect the presence of amyloid in different odontogenic cysts and tumors in correlation to matrix proteins secreted during enamel formation; namely amelogenin and odontogenic ameloblast‐associated protein. Methods This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Two cases of CEOT examined for β-catenin lacked nuclear immunoreactivity [ 29 , 30 ]. The presence of amyloid is considered characteristic of CEOT, but it should also be noted that such material is not specific for CEOT [ 31 , 32 ]. A recent study by Al-Qazzaz et al [ 32 ] revealed that, in addition to CEOT, various other odontogenic cysts and tumors, such as calcifying odontogenic cyst, ameloblastoma, adenomatoid odontogenic tumor, DGCT, and amyloid-rich subtype of odontogenic fibroma also produce amyloid in varying proportions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two cases of CEOT examined for β-catenin lacked nuclear immunoreactivity [ 29 , 30 ]. The presence of amyloid is considered characteristic of CEOT, but it should also be noted that such material is not specific for CEOT [ 31 , 32 ]. A recent study by Al-Qazzaz et al [ 32 ] revealed that, in addition to CEOT, various other odontogenic cysts and tumors, such as calcifying odontogenic cyst, ameloblastoma, adenomatoid odontogenic tumor, DGCT, and amyloid-rich subtype of odontogenic fibroma also produce amyloid in varying proportions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Al-Qazzaz et al [ 32 ] revealed that, in addition to CEOT, various other odontogenic cysts and tumors, such as calcifying odontogenic cyst, ameloblastoma, adenomatoid odontogenic tumor, DGCT, and amyloid-rich subtype of odontogenic fibroma also produce amyloid in varying proportions. In this study, multifocal amounts of amyloid were detected in one of the two DGCT cases tested [ 32 ]. Considering the potential relationship between DGCT and OCD, it seems plausible that focal or multifocal amounts of amyloid could be present in some OCDs.…”
Section: Discussionmentioning
confidence: 99%